AB0775 Has rituximab (RTX) a role in treatment of chronic non-renal henoch-schonlein purpura (HSP)? 9 years follow up of a patient with severe gastro-intestinal disease. (23rd January 2014) - Tosounidou, S.; Sahni, M.; Carruthers, D.
Abstract : Background: The clinical presentation of HSP is more severe among adults and tends to be atypical: higher rate of severe and atypical GI problems and delayed renal complications. Management in particular of refractory HSP remains controversial and results so far have been conflicting. We present a case of adult HSP with intractable GI involvement treated with repeat courses of Rituximab over the last 9 years. Efficacy of Rutiximab has been reported in 3 children 1 and 2 adult cases of refractory HSP but in all cases remission was achieved with 1- to 2 cycles of Rituximab. Our case is the first case reporting on the 9 year experience with RTX used as a remission maintenance therapy in HSP. Our case alongside with other reports suggests the use of RTX in non-ANCA vasculitis and highlights the need for studies of RTX as remission maintenance therapy in small vessel vasculitis and its long term safety profile. Objectives: A 61 year old female patient was referred to our centre in 2001 with progressive gut vasculitis and leucocytoclastic skin lesions, preceded by an 18 month history of abdominal pain, nausea, vomiting, haematochezia and palpable purpura. She also sustained right iliofemoral artery thrombosis and was fully anticoagulated. The diagnosis of HSP was confirmed by a skin and small bowel biopsy showing immune complex deposition, strongly stained for IgA. In 2002 she completed six cycles of Cyclophosphamide and was started on maintenance therapy with Azathioprine. However, she relapsed with severe GI symptoms and was treated with further eight cycles of Cyclophosphamide. Despite being heavily immunosupressed she continued to experience recurrent episodes of abdominal pain and haematochezia requiring treatment with intravenous methylprednisolone. In 2002 she received her first cycle of 500 mg RTX two weeks apart, resulting in clinical remission and was followed by Methorexate as a maintenance therapy. 11 months post RTX therapy she experienced further relapse of GI and skin symptoms. She has received repeat cycles since with a mean duration of 14 months in between the retreatment. In 2008 the patient developed severe haematemesis accompanied by acute right limb ischaemia requiring right tibial embolectomy. Subsequent endoscopy revealed presence of vasculitic lesions in the stomach. Again she responded well to RTX and stayed in remission for a year. Last relapse of severe GI symptoms happened in 2011 after 2 years of remission. Retreatment with RTX is usually given at onset of recurrent symptoms. Results: IgA plays a central role in pathogenesis of HSP and inhibition of IgA production might be a good approach to treat HSP. Although RXT should not deplete immunoglobulin secreting plasma cells, given its efficacy of Bcell depletion in other Bcell mediated disorder suggests use in refractory HSP. In our case the patient continues to be treated on demand with RTX therapy but the timing of retreatment remains unclear and this question expands to other type of small vessel vasculitis. It also remains unclear which remission maintenance treatment patient should receive following successful first remission induction with RTX to prevent relapses. Conclusions: RTX can be considered in cases of refractory HSP References: K Donnithorne et al. RTX for severe refractory chronic HSP. Disclosure of Interest: None Declared